Proceedings of the ACM SIGIR International Conference on Theory of Information Retrieval 2017
DOI: 10.1145/3121050.3121096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and Analyzing Click Simulation in Web Search

Abstract: We evaluate and analyze the quality of click models with respect to their ability to simulate users' click behavior. To this end, we propose distribution-based metrics for measuring the quality of click simulation in addition to metrics that directly compare simulated and real clicks. We perform a comparison of widely-used click models in terms of the quality of click simulation and analyze this quality for queries with di erent frequencies. We nd that click models fail to accurately simulate user clicks, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…For example, most click models are designed to optimize the likelihood of observed clicks. Although Malkevich et al [20] have shown that UBM is better than DBN in terms of click simulation, the ranker trained with DBN performed better than the ranker trained with UBM in our experiments. This suggests that optimizing click likelihood doesn't necessarily produce the best bias correction model for unbiased learning to rank.…”
Section: Comparison With Click Modelscontrasting
confidence: 78%
“…For example, most click models are designed to optimize the likelihood of observed clicks. Although Malkevich et al [20] have shown that UBM is better than DBN in terms of click simulation, the ranker trained with DBN performed better than the ranker trained with UBM in our experiments. This suggests that optimizing click likelihood doesn't necessarily produce the best bias correction model for unbiased learning to rank.…”
Section: Comparison With Click Modelscontrasting
confidence: 78%
“…The quality of click models is often evaluated by the Log-Likelihood and Perplexity [61], but also other reliability measures exist [62]. In previous work, click models have mainly been evaluated on semi-public web search datasets, e.g., from Yahoo!…”
Section: Click Modelsmentioning
confidence: 99%
“…3.4.1 Log-Likelihood. This is a standard evaluation measure of click models, and it was found that better scores correlate with a higher fidelity of simulated clicks [61]. We determine it over a run with |Q| queries and ranking length as follows:…”
Section: Evaluation Measuresmentioning
confidence: 99%
“…With a small compromise on the bottom of long ranked lists, MMF achieves superior performance and significantly outperforms the state-of-the-art fairness algorithms not only in top-k relevance, but also in top-k fairness. As most people would examine or only examine the top results on a result page [8,13,19,27], MMF is highly competitive and preferable in real LTR systems and applications.…”
Section: Introductionmentioning
confidence: 99%